The Effect of Spiritual Counseling on Hope in Patients with Multiple Sclerosis A Randomized Clinical Trial - Afshar, Mohammad (International journal of community based nursing and midwifery, 2021)
Copyright: © International Journal of Community Based Nursing and Midwifery.